(The Impact of Human Capital on Economic Growth of Sudan during the period (1999- 2017 - Mohammed, Ibrahim Abdul Rasool; Khader, Sumaya Awad; Bilal, Eve -Hawaa- Abdullah (Journal of Economic, Administrative and Legal Sciences, 2018)
The study titled as the impact of human capital on economic growth in Sudan during the period 1990- 2017 in order to analyze the relationship between human development and economic growth, the study employed descriptive and analytical method which based on time series data during the period of the study, also it employed Ordinary Least Square (OLS) technique to estimate the econometric model which depends on Endogenous Growth Model, the model was corrected from various statistical and econometrics problems. The results shows that, there is positive impact of employing modern technology on real production to enhance economic growth , human capital taken as total expenditure on education has positive impact on economic growth, while results shows an inverse impact of economic openness variable on economic growth as indicator for external factors, the study recommend the important of increases of government expenditure on education, encouragement of modern technology and apply more effective fiscal and monetary policy.